Comparison Analysis of the Health of BCA Syariah Bank and Indonesian Sharia Commercial Banks Using the Canel Method - Chessy Luviana Helmi; Suci Febriyanti; Ahmad Fauzul Hakim Hasibuan; Sri Ulina (Jurma : Jurnal Program Mahasiswa Kreatif, 2023)
This study aims to determine the level of soundness of Islamic Commercial Banks (BUS) in Indonesia using the Risk Based Bank Rating (RBBR) method or better known as RGEC method, including the Risk Profile, Acquisition and Capital of BUS in Indonesia 2015-2020. this type.This research is a descriptive research with a qualitative approach.The research results show that, the average BUS NPF ratio for 2015-2020 is 3.99%, indicating that BUS are in the healthy category. The smaller the NPF, the healthier the bank. The average ROA ratio for BUS 2015-2020 is 1.03%, shows that BUS is in a fairly healthy predicate. The greater the ROA, the healthier the bank.And the average 2015-2020 CAR ratio of 18.73% shows that BUS are in very healthy condition. predicate. The greater the CAR, the healthier the bank. This fact shows that the performance of BUS in’ Indonesia need to be improved so that the profit (ROA) is maximized. This study aims to determine the soundness of Bank BCA Syariah for the 2016- 2020 period in terms of each RGEC aspect (Risk Profile, Good Corporate Governance, Earnings, and Capital). This study uses descriptive analysis with a quantitative approach. The data used in this study comes from the Annual Report of Bank BCA Syariah from 2016-2020. Data analysis was performed by assessing the ratio rating of each RGEC aspect (Risk Profile, Good Corporate Governance, Earnings, and Capital). The results of further research will be calculated to obtain the RGEC composite value. The results showed that the health level of Bank BCA Syariah for the 2016-2020 period in terms of the Risk Profile aspect was ranked 2nd in the "Healthy" category.